Extraction of anti-hyperglycaemic bioactive compounds from Phyllanthus niruri L. through solvent mixture design: In vitro and in vivo evaluation - Ana Melissa Gonzalez Miragliotta; Gonzalo Adrián Ojeda; Romina Belén Gonzalez; Estela Rosa Jara; Gladys Pamela Teibler; Nélida María Peruchena; Ana María Torres (Elsevier, 2024)
Background: Species within Phyllanthus genus exhibit a diverse range of experimentally validated pharmacological activities. Notably, Phyllanthus niruri Linneo(Phyllanthaceae), commonly referred to as stonebreaker, is a native Central and South American species with a rich history of use in traditional ethnomedicine for treating gastrointestinal and renal disorders. Purpose: The aim of this study was to investigate the application of various solvent mixtures to optimize the extraction of anti-hyperglycemic secondary metabolites from P. niruri. Methods: To optimize the extraction of anti-hyperglycemic compounds from P. niruri, a solvent mixture design strategy was employed. The optimized extracts were subjected to chemical characterization using spectrophotometric methods and HPLC-DAD analysis. Also, the influence of edaphoclimatic conditions on the composition of extracts was investigated. The anti-hyperglycaemic potential of the extracts was evaluated through both in vitro and in vivo assays. The in vitro studies included enzyme inhibition assays targeting α-glucosidase from two sources (yeast and pig). For in vivo studies, a rat model with oral starch overload was used to confirm the anti-hyperglycaemic activity of the extracts. Results: An optimal solvent mixture (70 % methanol and 30 % ethyl acetate) was found as effective for extracting compounds with anti-hyperglycemic potential from P. niruri. All the extracts obtained using this solvent inhibited both, yeast and pig α-glucosidase, with greater selectivity for inhibiting the yeast-derived enzyme. Extracts from aerial parts (AP) exhibited the strongest inhibitory activity. These extracts contained phenolic compounds, specifically flavonoids, but no condensed tannins were detected. Chromatographic analysis of profile revealed a major peak consistent with corilagin. In vivo studies using a dose of 500 mg kg-1 demonstrated that this extract significantly reduced blood sugar levels after starch overload in rats. Conclusion: This study demonstrates the importance of selecting appropriate solvent mixtures to extract bioactive compounds with anti-hyperglycemic properties from P. niruri. Our findings support the traditional use of this plant as a anti-hyperglycaemic agent in ethnomedicine.